Advances in motivation in exercise and physical activity. - Hagger, Martin (Oxford University Press, 2012)
Given the considerable epidemiological evidence linking regular physical activity with good health and reduced risk of chronic disease, exercise psychologists have adopted theories and models of motivation to understand the antecedents and processes that give rise to health-related physical activity. These theories are important as they provide the basis for the development and evaluation of interventions aimed at promoting increased physical activity in a largely sedentary population. This chapter reviews three of the leading theories that have been applied in physical activity contexts: the theory of planned behavior, self-determination theory, and achievement goal theory. Advances in research that have aimed to promote better understanding of the factors that underpin motivation in physical activity and the relevant processes are also reviewed including implementation intentions, the increasing importance of psychological needs, and theoretical integration. In addition, the role of methodological improvements such as the measurement of implicit motivational processes and the need for ‘gold standard’ designs when evaluating physical activity interventions based on these theories are highlighted. It is concluded that future research needs to develop hybrid interventions adopting both motivational and implemental strategies to change physical activity behavior, research should extend knowledge of the relative contribution of implicit and explicit motivational processes on physical activity behavior, and investigations to evaluate physical activity interventions should pay careful attention to design and evaluation.